Perlindungan Pasien di Era BPJS Kesehatan - Firdaus, Firdaus (Ijtihad, 2018)
BPJS Health is a mandatory National Health Insurance imposed by the government to all Indonesian citizens to ensure that everyone is able to receive healthcare services. The first objective is to analyze patient protection under the said the Law No. 24 of 2011 on BPJS. The second objective is to identify the challenges of the implementation, management, and monitoring of the BPJS Health Insurance Institution. Findings from the study show that there are advantages and disadvantages in the BPJS Health system, as not all citizens are involved as participants. Further, the health services are unequal in respect of services rendered in different provinces in Indonesia. As a conclusion, the researcher had provided several recommendations from the legal and implementation aspects to strengthen the existing BPJS Health system, so that it can effectively protect all patients.